Improving continuity of care of patients with respiratory disease at hospital discharge. Issue 3 (September 2020) - Dummer, Jack; Stokes, Tim
Continuity of care refers to the delivery of coherent, logical and timely care to an individual. It is threatened during the transition of care at hospital discharge, which can contribute to worse patient outcomes. In a traditional acute care model, the roles of hospital and community healthcare providers do not overlap and this can be a barrier to continuity of care at hospital discharge. Furthermore, the transition from inpatient to outpatient care is associated with a transition from acute to chronic disease management and, in a busy hospital, attention to this can be crowded out by the pressures of providing acute care. This model is suboptimal for the large proportion of patients admitted to hospital with acute-on-chronic respiratory disease. In a chronic care model, the healthcare system is designed to give adequate priority to care of chronic disease. Integrated care for the patient with respiratory disease fits the chronic care model and responds to the fragmentation of care in a traditional acute care model: providers integrate their respiratory services to provide continuous, holistic care tailored to individuals. This promotes greater continuity of care for individuals, and can improve patient outcomes both at hospital discharge and more widely. Educational aims: To understand the concept of continuity of care and its effect at the transition between inpatient and outpatient care. To understand the difference between the acute and chronic models of healthcare. To understand the effect of integration of care on continuity of care for patients with respiratory disease and their health outcomes. The transition of care at hospital discharge is a time when continuity of care is threatened and this can contribute to adverse events. Increased integration of care by health providers at this time permits greater continuity of care and better outcomes. https://bit.ly/3iEIq0I